Environmental Challenges in Regions: Analysis and Measures to Reduce Potential Risks - Burmatova, Olga P. (Economy of Regions, 2021)
The environmental deterioration in Russia requires the identification and analysis of the main challenges facing the country and its individual regions in this sphere. Additionally, it is necessary to find ways to overcome these problems. The issue is particularly relevant for resource regions where new economic activities develop. the Lower Angara region in Krasnoyarsk krai is one of such regions. The study considers the environmental problems in connection with the socio-economic conditions of a particular territory. I used the method of economic and mathematical modelling based on the author's models for optimising environmental protection measures. The research combines the obtained results to built a comprehensive model of the future ecological situation that may develop in the region. The analysis discovered various causes of environmental challenges. The first reason is planning exxessive output at individual facilities. In particular, calculations have shown that in the conditions of the Lower Angara region, the unit capacity of the pulp and paper industry should not exceed 300-350 thousand tonnes (instead of the planned 720 thousand tonnes); the capacity of the aluminum plant should not exceed 200-250 thousand tonnes (instead of 600 thousand tonnes). Second, an excessive concentration of production in certain areas (primarily, in Boguchansky and Kodinsky industrial hubs) increases the environmental burden. Third, pollution control is complicated by unique production capacities of various facilities that require special purification systems. The fourth reason is the effects of synergism and additivity of contaminants. The fifth cause is the actual and potential negative consequences of the construction of hydropower plants on the Angara and Yenisei rivers. The results of this research can be used for creating a strategy for the integrated development of territorial economic systems to organise environmental protection activities and substantiate management decisions at the regional and local levels of governance.